2005
DOI: 10.1051/0004-6361:20041662
|View full text |Cite
|
Sign up to set email alerts
|

Class transitions and two component accretion flow in GRS 1915+105

Abstract: Abstract. The light curve of the galactic micro-quasar GRS 1915+105 changes in at least thirteen different ways which are called classes. We present examples of the transitions from one class to another as observed by the IXAE instrument aboard the Indian Satellite IRS-P3. We find that the transitions are associated with changes in photon counts over a time-scale of only a few hours and they take place through unknown classes. Assuming that the transitions are caused by variation of the accretion rates, this i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…In case of intermediate classes we have taken the hardness ratio of the harder portions. This sequence obtained from this Figure does not seem to have any special significance in that it does not support the observed class transitions reported in Chakrabarti et al (2004Chakrabarti et al ( , 2005. .…”
Section: Comptonizing Efficiency In Different Classes: An Unifying Viewcontrasting
confidence: 68%
See 2 more Smart Citations
“…In case of intermediate classes we have taken the hardness ratio of the harder portions. This sequence obtained from this Figure does not seem to have any special significance in that it does not support the observed class transitions reported in Chakrabarti et al (2004Chakrabarti et al ( , 2005. .…”
Section: Comptonizing Efficiency In Different Classes: An Unifying Viewcontrasting
confidence: 68%
“…Accepting the class XIII to be anomalous, we find from Fig. 4 that the observed transitions reported in Chakrabarti et al (2004Chakrabarti et al ( , 2005; Naik et al (2002b) are 'naturally' explained. For instance, χ → ρ (θ and β being anomalous and intermediate α has been reported by Naik et al (2002b)), ρ → α (β being anomalous) and κ → ρ, are expected from our analysis.…”
Section: Comptonizing Efficiency In Different Classes: An Unifying Viewmentioning
confidence: 74%
See 1 more Smart Citation
“…It is suggested that these LFQPOs must be linked to the properties of the accretion disk since their centroid frequencies are correlated with the disk flux (Markwardt et al 1999) while the emitted luminosity itself varies, for example due to changes in mass accretion rate (Tagger & Pellat 1999;Cabanac et al 2010). In Chakrabarti & Manickam (2000); Vadawale et al (2001); Rao et al (2000); Chakrabarti et al (2005) it was shown that the Comptonized photons produce QPOs and thus they are intrinsically related to spectral states.…”
Section: Introductionmentioning
confidence: 99%
“…On that occasion the source was in the ρ class for about five days, then changed to the κ class in which it remained for a similar time and afterwards returned to the former one. Transitions from/to the ρ class to/from other classes were described by Naik et al (2002), Chakrabarti et al (2004Chakrabarti et al ( , 2005, and Rodriguez et al (2008).…”
Section: Introductionmentioning
confidence: 99%